THE EFFECT OF EXTRACTION TIME ON THE YIELD OF FISH OIL MACKEREL TUNA (Euthynus affinis) EXTRACTED WITH WET RENDERING METHOD - Fadli Khairullah; Edison Edison; Mirna Ilza (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTExtraction is one way to produce fish oil. The temperature used in the extraction process affects the characteristics of the oil. One of the extraction methods to get fish oil is dry rendering. Extraction temperature can affect the yield. This study aims to determine the appropriate temperature using dry rendering extraction of the resulting yield value. The research method used is an experimental method using a non-factorial completely randomized design. The treatment used consisted of 3 levels, namely 70 oC (K1), 80 oC (K2), and 90 oC (K3) with a duration of 1 hour. The analyzed parameter is yield. The results obtained that the extraction of mackerel fish oil using the dry rendering method and treatment at temperatures of 70°C, 80°C, and 90°C had yield values of 3.09%, 4.62%, and 5.22, respectively. %,. The highest yield of tuna fish oil was produced at a temperature of 90oC. The difference in the extraction temperature of tuna oil has an effect on the yield of the oil obtained. Keywords: Dry Rendering Extraction, Temperature, Yield.